Factors Associated With Smoking And Diabetes Mellitus Linked To Increased Mortality And Morbidity: A Study In Guangdong, China - Xueming, Sun; Che Hassan, Datin Hafizah; Mohd Said, Faridah (Cuestiones de Fisioterapia, 2023)
About 34% of the people in guangdong province, china, smoke, and about 20.8% of the people have diabetes. This is a big public health problem. Both of these rates are higher than or equal to the national averages. Smoking cigarettes raises the chances of getting diabetes mellitus, which also raises the chances of being ill or dying in the general population. This inquiry was the impetus for conducting this research initially. The purpose of this research was to find out whether smoking increases the chance of getting diabetes. Case-control studies have not sufficiently examined the association between smoking and diabetes in chinese communities where such a correlation exists. Researchers in guangdong conducted a case-control study to examine the association between habitual cigarette smoking and the onset of diabetes. The results show that there is a clear dose-response relationship and that heavy smokers are more likely to get diabetes than non-smokers in the community. These results are quite similar to what previous studies in china and other countries have shown. The first thing that stands out to the reader is that smoking is connected to metabolic disorders like diabetes and more prevalent but potentially deadly conditions like heart disease and lung disease. These strategies may help lessen the effects of these problems. The goals of these treatments should be to lower the number of individuals who smoke and ameliorate the diabetes epidemic. In light of all the evidence, the results of the case-control studies done in guangdong add to the increasing body of evidence that smoking cigarettes considerably increases the chance of getting diabetes.